DAMPAK KEBIJAKAN PEMBANGUNAN JALAN BOULEVARD AMURANG KABUPATEN MINAHASA SELATAN - TUMIWA, PINGKAN; LENGKONG, FLORENCE DAICY; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2020)
Community empowerment is a development process in which the community takes the initiative to startthe process of social activities to improve the situation and condition of oneself so that the communitybecomes independent. Coastal communities are people who live in coastal areas and their livelihoods ofthe economy depend directly on the utilization of marine and coastal resources through available fishingand cultivation activities. In this study using a type of qualitative research in which this research isdescriptive in nature that is conducting in-depth interviews collecting primary data and collectingsecondary data, i.e. then the results of primary and secondary data are processed and data will beobtained. The results showed that the problem hampering the empowerment of coastal communities inInobonto Dua Village Bolaang Mongondow District was where the government both the BolaangMongondow District Fisheries Office and the village government had provided programs in the form oftraining and assistance to coastal communities in Inobonto Dua Village but in the problem the communityis not good enough managing the assistance that has been provided and the community is not goodenough to implement the training that has been given by the government to the coastal communities. Andalso coastal communities are not good in terms of independence because most people are still dependenton government assistance and do not want to be independent themselves and coastal communities also stillexpect work calls from other communities to become helpers or workers for them to make money. This hasbecome the majority of the people who are not independent because they are unable to apply what thegovernment has given to them which results in a low economy and increased poverty in Inobonto DuaVillage Bolaang Mongondow Regency.Keywords : Impact, Policy, Development, Infrastructur, Road